Space-Occupying Lesions of the Inner Ear Are Easily Misdiagnosed as Endolymphatic Hydrops in a Perilymph-Enhanced Sequence Without the Assistance of a Heavily T2-Weighted Sequence. Issue 5 (3rd September 2022) - Chen, Wei; Niu, Yue; Lin, Mengyan; Geng, Yue; Lin, Naier; Wang, Xiaolin; Sha, Yan
Abstract : Objective: The aim of the study was to explore the value of T2-sampling perfection with application-optimized contrasts by using different flip angle evolutions (T2-SPACE) in identifying space-occupying lesions of the inner ear. Methods: We collected the T2-SPACE and 3-dimensional inversion-recovery sequence with real reconstruction (3D-real IR) images of 220 patients with inner ear symptoms, including 15 patients with inner ear space-occupying lesions. With T2-SPACE images hidden, a senior and junior radiologist made a diagnosis for all patients using only the 3D-real IR images. After 4 weeks the images were shuffled, and T2-SPACE images were made available to the 2 radiologists in addition to 3D-real IR to reconsider the diagnosis for all patients. Results: With the SPACE images hidden, the correct diagnosis rate of the space-occupying lesions was 8/15 (53.3%) for the senior radiologist, whereas it was only 2/15 (13.3%) for the junior radiologist. Without the SPACE images hidden, the correct diagnosis rate of the space-occupying lesions was 15/15 (100.0%) for the senior radiologist, whereas it was 13/15 (86.7%) for the junior radiologist. Of the 15 patients, 7 had only vestibular space-occupying lesions, 2 had only cochlear space-occupying lesions, and 6 had both. No semicircular canal space-occupying lesion was observed. Conclusions: T2-SPACE can help identify space-occupying lesions of the inner ear that tend to be misdiagnosed as endolymphatic hydrops on 3D-real IR. The senior radiologist had a higher rate for the identification of space-occupying lesions than the junior radiologist when using only 3D-real IR, although the senior radiologist detection rate was still only 53.3%. With the addition of T2-SPACE, both the junior and senior radiologist achieved a high detection rate, which increased to 86.7% and 100%, respectively.